Analisis Determinan Purchase Intention Album Musik Fisik di Era Digital Menggunakan E-WOM, Perceived Quality, Brand Image, dan Brand Trust - Fayza Abia Kamila; Usep Suhud; Nofriska Krissanya (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the influence of electronic word of mouth (e-WOM), perceived quality, brand image, and brand trust on purchase intention of Enhypen's physical music albums in the digital era. The rapid growth of digital music streaming platforms has shifted consumer behavior away from physical album purchases, yet physical albums remain a niche market for loyal fans and collectors, particularly in the K-pop industry. This research employs a quantitative approach with a survey method. Data were collected from 261 respondents who are Engene (Enhypen fans) residing in the Jakarta administrative area, aged 18-29 years, and actively following K-pop trends online for the past four to five years, using a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS software. The results indicate that e-WOM, perceived quality, brand image, and brand trust each have a positive and significant effect on purchase intention. Furthermore, e-WOM and brand image also positively and significantly affect brand trust. All seven hypotheses proposed in this study were accepted. These findings provide strategic implications for music industry marketers, particularly entertainment agencies, to strengthen brand communities, enhance perceived product quality, build positive brand image, and maintain long-term brand trust to sustain physical album sales in the digital age.